Praktik Pengelolaan Dana Konsumsi Mahasiswi STIS Hidayatullah Balikpapan - Sitti Masitha Masykur; Ummi Kalsum Tono; Azzah Amani Alhanun (LPPM STIS Hidayatullah, 2023)
The high cost of education becomes a burden for economically disadvantaged students so many PTN and PTS provide subsidies. STIS Hidayatullah is one of the private universities that provides subsidies for its students. This study aims to determine the practice of subsidies that occur among female students of STIS Hidayatullah Balikpapan. This research is field research with a qualitative descriptive method. The object of this research practice is the practice of managing consumption funds and subsidies according to Islamic law. The results of this study indicate that the subsidies at STIS Hidayatullah are in the form of reduced consumption fees by the amount determined by STIS with the agreement of both parties. The discount is tabarru 'or alms which is recommended in Islam. The management of consumption contribution funds is also by Islamic law principles.